Postnatal growth and body composition up to two years of age of term and preterm infants with placental insufficiency and/or small size for gestational age at birth - Wenhold, Friedeburg Anna Maria (University of Pretoria, 2024)
Thesis (PhD(Dietetics))--University of Pretoria, 2024.